Processing Nano-YSZ in Solid Oxide Fuel Cells: The Effect of Sintering Atmosphere on Thermochemical Stability. Issue 2 (1st January 2019) - Muhoza, S. P.; McCormack, A.; Garrett, R. W.; Yuce, M. D.; Prathab, V. S.; Hambright, S. K.; Cottam, M. A.; Gross, M. D.
Abstract : The thermochemical stability of nanoscale yttria-stabilized-zirconia (nYSZ), processed via in situ carbon templating, was studied between 850°C–1350°C in four sintering atmospheres: Ar, N2, H2, and humidified H2 . The in situ carbon templating method generates nanoscale ceramic particles surrounded by an amorphous carbon template upon sintering. The carbon template is subsequently removed by low temperature oxidation, leaving behind nanoscale ceramic particles. In Ar and H2, a ZrC impurity formed at temperatures ≥1150°C. In humidified H2, either a ZrC impurity formed or the carbon template oxidized. In N2, ZrC was not observed over the temperature range studied and the carbon template was preserved. After carbon template removal, the nYSZ surface areas were high for Ar, H2, and N2 : 55–99 m 2 ·g −1 . For humidified H2, nYSZ surface area decreased as the carbon template was lost. Finally, nYSZ, processed in N2 at 850°C and 1250°C, was integrated into symmetric YSZ-Lanthanum Strontium Ferrite (YSZ-LSF) cathode cells. The addition of nYSZ decreased cathode non-ohmic resistance, at 550°C in air, by 40% and 27% for nYSZ processed at 850°C and 1250°C, respectively. This work demonstrates that N2 is a thermochemically stable atmosphere for in situ carbon templating and that the resulting nYSZ considerably improves electrode performance.